Conservative ministers in the Coalition government of 2010–15: evidence of bias in the ministerial selections of David Cameron?. Issue 3 (2nd July 2016) - Heppell, Tim; Crines, Andrew
ABSTRACT: The article uses a data set of the 2010–15 Parliamentary Conservative Party (PCP) to test a series of hypotheses in order to determine whether those selected for ministerial office during the coalition era were representative of the PCP as a whole. The findings show no significant associations or bias by Cameron in terms of age, schooling, regional base, morality, voting for Cameron in the Conservative Party leadership election and, most significantly, gender. Significant associations or bias were evident in terms of Cameron's patronage with regard to university education and electoral marginality. The findings demonstrate that any critique of current Conservative ministers based on their supposed elitism stems from the institutional and structural biases within the Conservative Party at candidate selection level, and cannot be attributed to bias on behalf of Cameron.